The origins and management of erotic countertrasference and its impact on the therapeutic alliance : a critical investigation of the psychoanalytic literature. - Johnstone, Candice (My University, 2010)
In certain instances both male and female analysts may develop an erotic countertransference during the course of analysis. This theoretical research project sought to explore the meaning and manifestation of erotic countertransference in psychoanalytic treatment. Information was gathered from a variety of psychoanalytic literature sources in order to include a broad coverage of psychoanalytic approaches to issues concerning the origins and handling of erotic countertransference within the therapeutic setting. Analysts may experience both idealising, sexual, and loving feelings, as well as feelings of hostility and hate in the erotic countertransference response. Erotic countertransference feelings were found to originate from various psychosexual developmental stages, internal objects relations and may also be experienced due to projective identification, narcissistic tendencies in analysts as well as being influenced by the genders of patient and analyst in the dyad. However, it was noted that a complicating factor in identifying why an erotic countertransference occurs is the mutual influence of unconscious dynamics of both patient and analyst. This has implications for how the erotic countertransference may be most effectively and ethically handled. A specific debate concerning self-disclosure of analysts’ sexual feelings from a relational psychoanalytic perspective versus maintaining analytic abstinence was included and it was found that self-disclosure of analysts’ sexual feelings is a problematic technique in the psychoanalytic therapeutic context. The findings of this research report may provide some containment for analysts who experience sexual feelings for patients by offering an explanation of the complexity of erotic countertransference and recommendations on how it may be managed.